Integrating Media and Technology in PAI Learning - M. Sauqi Iza Masruri; Arif Andika (Journal of International Multidisciplinary Research, 2024)
After the end of the Covid 19 epidemic in 2021, PAI learning is still seen as a boring lesson because there is still a lot of conventional use of the scavenger. It encourages PAI teachers to quickly transform using learning based on media and technology integration. The purpose of writing this article is to show the meaning of Media and technology integration in PAI learning that is useful in making PAI training that has been conventional to be innovative, creative and effective. The results of this research are: 1) Media and technology integration refers to the integration or integration of learning media and technology (application-application learning) either in the form of tools, materials, or other elements that help students in understanding learning materials. The main purpose of this integration is to facilitate students in receiving information/material in PAI learning. 2)Media and technology integration in PAI learning plays a role and function in combining media and technology with PAI subjects to improve quality and quality in the teaching process. 4) Factors driving the use of media and technology in PAI learning highlight the need for innovative and technology-based approaches to address the challenges of diversity, embrace the digital revolution, integrate religion and science, overcome the lack of PAI, and improve the curriculum component. 5) Real examples of the integration of media and technology through various types of applications such as Kahoot, youtube, whatsaap, flipbook and so on proved to have a huge influence and give positive impact sharing in the world of Islamic Religious Education.